Gender perspective in creative search (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
I share same reflections on stage creation. I do it as a woman, but I don't do it from a binary perspective of view. I speak from that label because I still inhabit it, because I keep resignifying it. In a context where I believe transformation is possible. How do we think ourselves today when confronted by an artistic artwork? Along this interpellation new expressions and creative processes, new dramaturgies, new relations with us and with others arise.
Keywords: Gender perspective; Performing arts; Creative processes